THE GUT–BRAIN AXIS: THE INFLUENCE OF THE INTESTINAL MICROBIOME ON NEUROINFLAMMATION AND MENTAL HEALTH - Anderson Leandro Kovalski; Naiara Cristina de Souza Garajau; And Karollyne Araújo Coelho; Eluza da Mota Ramos; Oldair Donizete Galeni; Fernanda Aparecida Meirinho; Karla Julião Villani Felippe; Gabriel Lopes Madeira Nascimento; Mariana Castro Nunes; Isabelle Cristina de Oliveira Vieira (Artefactum - revista de estudos interdisciplinares, 2026)
The gut-brain axis is a complex bidirectional communication system between the gastrointestinal tract and the central nervous system, in which the intestinal microbiota may contribute to the modulation of immune, metabolic, neuroendocrine, and neural processes. This study aimed to analyze evidence on the relationship between the intestinal microbiome, neuroinflammation, and mental health. This qualitative integrative review consulted PubMed, Scopus, and SpringerLink, with complementary searches in the Diadorim and Miguilim portals. Publications in Portuguese and English from 2021 to 2026 were considered, and 16 studies composed the analytical synthesis. The findings indicated associations between intestinal dysbiosis, changes in inflammatory responses, modulation of neuroactive pathways, and symptoms related to depression, anxiety, and other neuropsychiatric disorders. Nutritional interventions and strategies investigated in the field of psychobiotics showed potential as adjunctive measures; however, the studies were heterogeneous and do not support standardized clinical protocols. The evidence therefore supports biological plausibility and relevant associations between the microbiome and the gut-brain axis, but it does not establish a definitive causal relationship or justify replacing conventional treatments.